Pengaruh pendidikan kesehatan bagi ibu terhadap asupan energi, aktivitas fisik dan indeks massa tubuh pada anak kelebihan berat badan - Haya, Miratul; Setiawati E, Mexitalia; Margawati, Ani (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2015)
Background : The percentage of overweight children in Bengkulu (16.4%) is higher than the national (11.9%). Factors causing overweight is a high energy intake and low physical activity.Objective : To analyze the impact of health education for mothers in changes of maternal behavior, energy intake, physical activity level and Body Mass Index (BMI) z-score among overweight children 3-6 years old.Methode : Quasi-Experiment with non-randomized pre-post test control group design. Subjects (48 mothers) were selected purposively and divided into 2 groups (treatment and control). Health education in the treatment group was conducted 6 times in 12 weeks. Analyses were conducted by Independent t-test, Mann Whitney, Paired t-test, Wilcoxon and Covariance.Results: There was an increased in attitude score (20.9 ± 3.52), carbohydrate intake percentage (3.7 ± 7.30%) and physical activity level (0.04 ± 0.01) in the treatment  group. The energy  adequacy  level (-3.4 ± 13.26%)  and BMI z-score (-0.57 ± 0.26) decreased in the treatment group. There were difference between the treatment and control groups in attitude, energy adequacy level, physical activity level and BMI z-score after intervention (p <0.05).Conclusion: Health education for mothers affect the positive change in mother attitude in terms of the overweight children treatment and increased physical activity level, decreased energy adequacy level and BMI z-score in overweight children.